STRATEGI PENINGKATAN MUTU SEKOLAH BERDASARKAN ANALISIS SWOT DI SEKOLAH MENENGAH PERTAMA - Sujoko, Edi (Kelola: Jurnal Manajemen Pendidikan, 2017)
This research was a research and development study. The purpose of this research are (1) Describe what factors are the strengths, weaknesses , opportunities and threats in improving the quality in SMPN1 Bawen ;(2) Develop a strategy that needs to be done to improve the quality SMPN1 Bawen based on SWOT analysis. Data was collected through interviews, observation, study of document and focus group discussion (FGD). The results of the SWOT analysis is to improve the quality of schools stated position SMPN1 Bawen be in SO quadrant, which supports an aggressive strategy to support the growth of the school created a strategic plan that leverages the power to capture the opportunities that exist . Draft strategic aspects: inputs, processes, and outputs include: developing the ideal school environment, through programs 7 K ( Health, Order, Beauty, Shade, Security, Comfort, and Kinship ; Optimization of teacher professional development programs, and improve academic achievement and non- academic as optimal as possible.